Предмет: Алгебра,
автор: HappyPrincess14
упростите выражение (2a+b)*(a-b)-(2a^2-b^2) и найдите его значение при a=2,b=-1/2
Ответы
Автор ответа:
0
(2a + b)(a - b) - 2a^2 + b^2 =
= 2a^2 - 2ab + ab - b^2 - 2a^2 + b^2 =
= - 2ab + ab
- 2*2*(-1/2) + 2*(-1/2) = 1
= 2a^2 - 2ab + ab - b^2 - 2a^2 + b^2 =
= - 2ab + ab
- 2*2*(-1/2) + 2*(-1/2) = 1
Похожие вопросы
Предмет: Математика,
автор: dasabozko345
Предмет: Математика,
автор: lizkaskidan2
Предмет: Математика,
автор: smuzi14
Предмет: Биология,
автор: Вера1909
Предмет: Литература,
автор: Nastenaalania